Impact of Resveratrol on Glucose Control, Hippocampal Structure and Connectivity, and Memory Performance in Patients with Mild Cognitive Impairment - Köbe, Theresa; Witte, A. Veronica; Schnelle, Ariane; Tesky, Valentina A.; Pantel, Johannes; Schuchardt, Jan-Philipp; Hahn, Andreas; Bohlken, Jens; Grittner, Ulrike; Flöel, Agnes (Frontiers in Neuroscience, 2017)
In healthy older adults, resveratrol supplementation has been shown to improve long-term glucose control, resting-state functional connectivity of the hippocampus, and memory function. Here, we aimed to investigate if these beneficial effects extend to individuals at high-risk for dementia, i. e., patients with mild cognitive impairment. In a randomized, double-blind interventional study, forty well-characterized patients with mild cognitive impairment (21 females; 50-80 years) completed 26 weeks of resveratrol (200mg/d; n=18) or placebo (1015mg/d olive oil; n=22) intake. Serum levels of glucose, glycated hemoglobin A1c and insulin were determined before and after intervention. Moreover, cerebral magnetic resonance imaging (3T) (n=14 vs 16) was conducted to analyze hippocampus volume, microstructure and resting-state functional connectivity, and neuropsychological testing was conducted to assess learning and memory (primary endpoint) at both time points. In comparison to the control group, resveratrol supplementation resulted in lower glycated hemoglobin A1c concentration with a moderate effect size (ANOVARM p=0.059, Cohen´s d=0.66), higher resting-state functional connectivity between right anterior hippocampus and right angular cortex (p<0.001), and led to a moderate preservation of left anterior hippocampus volume (ANOVARM p=0.061, Cohen´s d= 0.68). No significant differences in memory performance emerged between groups. This proof-of-concept study indicates for the first-time that resveratrol intake may reduce glycated hemoglobin A1c, preserves hippocampus volume, and improves hippocampus resting-state functional connectivity in at-risk patients for dementia. Larger trials with longer intervention time should now determine if these benefits can be validated and extended to cognitive function.